2016
DOI: 10.3329/updcj.v5i2.27265
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of periodontal diseases among the patient visiting at Periodontology OPD Update Dental College Hospital, Dhaka

Abstract: Objective: The aim of the study was to investigate the prevalence of periodontal diseases with regards to the age and sex in population around a dental hospital, and to compare the results with national and international studies.Methodology: A cross sectional study was initiated to characterize the demographic, oral health behavior. Prevalence of different types of periodontal diseases was evaluated in the out patients periodontology department of Update Dental College and Hospital Dhaka, Bangladesh. Investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Worldwide people have periodontal disease usually elderly people suff ered more while some other forms of diseases appear at quite a young age [29][30][31]. Evaluation of the general incidence among the adults population showed that 50.0 to 100.0% of people suff ered from gingivitis [32].…”
Section: Resultsmentioning
confidence: 99%
“…Worldwide people have periodontal disease usually elderly people suff ered more while some other forms of diseases appear at quite a young age [29][30][31]. Evaluation of the general incidence among the adults population showed that 50.0 to 100.0% of people suff ered from gingivitis [32].…”
Section: Resultsmentioning
confidence: 99%
“…Research on the oral health of tribal elderly individuals in Bangladesh has shown that they have a higher incidence of oral health issues compared to the general population [29][30][31]. One study found that almost 75% of tribal elderly individuals in Bangladesh had at least one decayed or missing tooth, and over 50% had periodontal disease [32,33]. This contrasts with the national average, where only about 60% of older adults have at least one decayed or missing tooth and around 25% have periodontal disease [32,34,35].…”
Section: Introductionmentioning
confidence: 99%
“…Because of poor oral hygiene practices, betel quid chewing & complication of different systemic diseases, periodontal diseases become more prevalent among all dental problems in Bangladesh. (3)(4)(5) This type of patient is commonly treated here by phase-1 nonsurgical therapy mainly by scaling, polishing, and oral hygiene instructions and given antimicrobial therapy. (6) flap surgery is indicated if the periodontal condition is not improved by non-surgical periodontal therapy.…”
Section: Introductionmentioning
confidence: 99%